INDONESIAN FOOD SECURITY POLICY - Limenta, Michelle Engel; Chandra, Sianti (UI Scholars Hub, 2017)
Food security has been an issue of endless discussions given its sensitive nature of being associated with the wellbeing of individuals. Pursuant to Article 33 of the Indonesian Constitution, the Indonesian Government, in principle, have the legal capacity to utilize to the greatest extent the nation’s natural resources for the sake of the welfare of Indonesian citizens through regulating and issuing relevant policies. As regards food security, Indonesian policies, in general, have been more focused on programs that aim to promote self-sufficiency in food production in order to achieve food security, as stated in Law No. 18 of 2012 regarding Food. The Law provides that importing food products can only be conducted if production by local producers is insufficient for the consumption needs of Indonesian citizens. Thus, this article will discuss further the national and international implications as a result of the government’s continuous perception that food security problems can be resolved with self-sufficiency in food production. The question is whether this policy has managed to reach its intended goal, namely ensuring Indonesian citizens the availability and access to nutritious food? Finally, this article will offer two solutions that are deemed to be more effective and efficient than the notion of food self-sufficiency in achieving the food security policy objective.